Cinema of the Borders : New Yugoslav Post-War Cinema - Borjan, Etami (2010)
The new nation states, formed in the 90’s, had to be re-defined through ideological, cultural, historical and national “revitalization”, a process in which media, especially cinema, played a pivotal role. The outburst of ethnic nationalisms in postwar Yugoslavian countries, the emerging problems of constituting and defining the new national and ethnic boundaries in a multicultural, multilingual and multiethnic environment, was very well evidenced in the film production of the last two decades. The aim of the paper is to demonstrate the main tendencies in the film production of the new post war Yugoslavian cinemas in the last two decades and to discuss the problems related to the actual position of these cinemas within European context. Cinema is a tool for the production of culture but it also represents the dynamics of cultural production. The paper analyzes the mechanisms of discursive formations of national identities through cinema and the impact that the cinemas of the borders have had in the re-negotiation of the territorial and cultural limits of Europe.
Projekt MZOS
ENG